2021
DOI: 10.1097/cm9.0000000000001825
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the oral microbiome in HIV infection: causes, effects and potential interventions

Abstract: A massive depletion of CD4 + T lymphocytes has been described in early and acute human immunodeficiency virus (HIV) infection, leading to an imbalance between the human microbiome and immune responses. In recent years, a growing interest in the alterations in gut microbiota in HIV infection has led to many studies; however, only few studies have been conducted to explore the importance of oral microbiome in HIV-infected individuals. Evidence has indicated the dysbiosis of oral microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 122 publications
0
30
0
Order By: Relevance
“…Furthermore, increased Proteobacteria and decreased Firmicutes in HIV have also been reported [38]. Additionally, there have been inconsistencies in the reporting of the oral microbiome between HIV infected patients and healthy controls [42]. Jimenez-Hernandez et al reported that the salivary alpha diversity in HIV-infected individuals were significantly higher than those in HIVuninfected samples [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, increased Proteobacteria and decreased Firmicutes in HIV have also been reported [38]. Additionally, there have been inconsistencies in the reporting of the oral microbiome between HIV infected patients and healthy controls [42]. Jimenez-Hernandez et al reported that the salivary alpha diversity in HIV-infected individuals were significantly higher than those in HIVuninfected samples [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased Proteobacteria and decreased Firmicutes in HIV have also been reported [38]. Additionally, there have been inconsistencies in the reporting of the oral microbiome between HIV infected patients and healthy controls [42]. Jimenez-Hernandez et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the new insights into the role of the latter in periodontal diseases and systemic diseases including cardiovascular diseases ( Peng et al, 2022 ). Results in HIV infection have been inconsistent and contradictory ( Li et al, 2021 ). One study looking at the oral microbiota in ART-treated PLWH found that HIV influenced the oral bacterial communities, albeit this influence was smaller compared to clinical variables like gingivitis, smoking, periodontitis, and antibiotics, which collectively had a stronger significant effect ( Griffen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in oral bacterial communities and virome in HIVinfected individuals have been reported in many studies (4,5,(20)(21)(22). The possible reasons for oral microbiome dysbiosis might be the disrupted oral immunity caused by HIV infection, including changes in secretory components in saliva, deficiency of innate immune responses and adaptive immune responses (5).…”
Section: The Oral Mycobiome In Hiv Infectionmentioning
confidence: 99%